Sustained-release pramipexole in the treatment of Parkinson’s disease - Natalia Vladimirovna Fedorova (Неврология, нейропсихиатрия, психосоматика, 2012)
Dopamine (DA) receptor agonists ensure stimulation of DA receptors in the brain, by compensating for dopaminergic deficiency in Parkinson’s disease (PD). Since 1996, pramipexole has been used to treat early and extensive PD stages; its clinical efficacy has been proven in many double-blind randomized placebo-controlled and open-labeled trials. Since 2009 the European countries and the USA has used extendedrelease pramipexole (ERP) that is given once daily. Its benefits are stabilized plasma drug concentrations, 24-hour action, which provides continuous dopaminergic stimulation ofpostsynaptic receptors for the prevention and therapy of already existing motor fluctuations and drug-induced dyskinesias. Once-daily dosing of ERP increases the adherence of a patient with PD to regular treatment. Two (extended- and immediate-release) formulations of pramipexole differ only in the release rate for the active ingredient from the contents of a tablet. Both formulations contain the same active ingredient, have the similar profile of interacting with DA receptors, and show pharmacotherapeutic efficacy.